Revitalización de la cultura indígena "Cayambi" para enriquecer nuestra identidad: lengua y vestimenta en los niños/as del 6to a 7mo año de educación básica del CECIB Tarquino Idrobo de la comunidad de Ugsha. - Pupiales Pupiales, Elba Marina (2013)
For the development of this project we have made the first diagnosis is concerned with the leaders and residents of the community where we do the socialization of the importance of culture within the family and education, some of them also had a majority participation to be the subject of cultural revitalization Cayambi both Quechua language and clothing to children / as the sixth and seventh year of basic education CECIB Idrobo Tarquin Ugsha community.